Implicit Teacher Theories Regarding the Argumentative Commentary of Multimodal Texts in the Teaching of Spanish as a Native and Foreign Language - Caro Valverde, María Teresa; Amo Sánchez-Fortún, José Manuel de; Domínguez-Oller, Juana Celia (Frontiers in Psychology, 2021)
This research explores and interprets the implicit theories of teachers that influence their decision-making on educational practice in the classroom and on the academic performance of students. Specifically, it focuses on the analysis of the belief system of Spanish teachers about the development of argumentation in the commentary of multimodal texts attending to typological parameters of traditional, technical, active, constructivist and critical pedagogical models. For this, a quantitative methodology based on non-experimental or ex post facto design with semi-structured and closed survey-questionnaire-type instruments has been selected. From a target population made up of Spanish teachers, 502 respondents selected using the non-probabilistic sampling technique applied the accessibility criterion. An ad hoc questionnaire made up of 28 items structured in two blocks has been prepared: the first aimed at establishing the sociodemographic and professional profile of the participants and the second at collecting data related to their beliefs regarding the argumentative work of the text comment in class (definition, didactic modality, expression and argumentative understanding, statement value, keys and resources). The results show that the majority declare to align themselves with non-conservative didactic trends or approaches, centered on the student body and oriented to the construction of critical knowledge, but their pragmatic preferences reveal the persistence of the hidden curriculum of traditional and technical teaching. Such a contradiction between his explicit and implicit epistemological convictions hampers his coherent progress towards the emancipatory theory proper to a critical model of communicative quality. It is also verified that the findings of this study offer guidelines for the design of an effective and efficient training proposal on the competent use of argumentation in text commentary.